Effects of distillers dried grains associated with high and low forage fiber level on performance of dairy cows - Viana, Vinicius de Sena Sales (2020)
The objective of this study was to evaluate the effects of increasing levels of distillers dried grains (DDG) in high and low forage neutral detergent fiber (NDFf) levels on intake, digestibility, feed sorting behavior, milk yield and composition, hormonal profile, and economic analysis of the diets. Twelve Holstein cows were assigned to a replicated 6 × 6 Latin squares with a 3 × 2 factorial arrangement of treatments. Diets were formulated with 0, 20, and 40% DDG on dry matter (DM) basis with low forage (21% NDFf) or high forage (31% NDFf). Cows fed diet with lower inclusion level of NDFf had the greatest DM intake. Dry matter intake and other nutrients intake were lower at inclusion of 40% DDG than 0 or 20% DDG. Dry matter, organic matter, and crude protein digestibility was inversely proportional to increasing DDG levels. In addition, there was a decrease in crude protein ruminal digestibility when increasing DDG level. The cows submitted to the treatments with 40% of inclusion of DDG refused the concentrated ration of the diet. Distillers dried grains did not affect ruminal pH. The inclusion of up to 20% DDG does not affect the intake and digestibility of dairy cows. About milk yield, we observed similar results for cows fed diets with 0 and 20% of DDG. Milk protein decreased with increasing inclusion of DDG in the diet. We observed no effect of diets for milk fat concentration. We also did not observe difference for microbial protein synthesis among treatments. We found a reduction in plasma glucose with an increase of DDG level. Total plasma cholesterol concentration increased with the greater level of DDG in diet. However, plasma urea concentration was reduced with the increase of DDG in diet. The nitrogen balance presented a negative value for all treatments, except for the animals fed with 0% DDG and the lowest NDFf level. According to income over feed cost analysis, we observed an economic advantage when feeding 20% DDG diets compared with 0 and 40% DDG diets. The inclusion up to 20% DDG does not affect the productive performance of dairy cows and may be an alternative of feeding dairy cows. Keywords: Alternative feeds. Coproducts etanol. Dairy yield.